2014
DOI: 10.1111/pce.12376
|View full text |Cite
|
Sign up to set email alerts
|

How changing root system architecture can help tackle a reduction in soil phosphate (P) levels for better plant P acquisition

Abstract: 19The readily available global rock phosphate (P) reserves may run out within the next 50-130 20 years, causing soils to have a reduced P concentration which will affect plant P uptake. Using 21 a combination of mathematical modelling and experimental data we investigated potential 22 plant-based options for optimising crop P uptake in reduced soil P environments. 23By varying the P concentration within a well-mixed agricultural soil, for high and low P (35.5 24 to 12.5 mg l -1 respectively, using Olsen's P in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 50 publications
0
34
0
Order By: Relevance
“…Greater lateral root branching increases the rate at which a soil domain is depleted of resources, especially for immobile resources like P. For example, results from a recent modeling study showed that a greater density of lateral branches in the topsoil can improve P uptake from low-P soil in wheat (Triticum aestivum) by 142% (Heppell et al, 2015). However, for highly mobile resources, like N and water, depletion zones are larger and the greater lateral root branching creates overlapping resource depletion zones around roots of the same plant, thereby decreasing resource capture efficiency (Ge et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Greater lateral root branching increases the rate at which a soil domain is depleted of resources, especially for immobile resources like P. For example, results from a recent modeling study showed that a greater density of lateral branches in the topsoil can improve P uptake from low-P soil in wheat (Triticum aestivum) by 142% (Heppell et al, 2015). However, for highly mobile resources, like N and water, depletion zones are larger and the greater lateral root branching creates overlapping resource depletion zones around roots of the same plant, thereby decreasing resource capture efficiency (Ge et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, P promotes the development of roots; thus, the growth of Chinese cabbage roots was significantly improved after the application of YL6 (Chen et al, 2017). The root is the main organ for absorbing minerals and water and participates in material transport (Shane et al, 2003; Heppell et al, 2015). Therefore, it is easy to understand that the fresh and dry plant weight and plant height were significantly increased with the improved root system.…”
Section: Discussionmentioning
confidence: 99%
“…To run the adapted mathematical model a set of parameters were taken from Roose and Fowler (2004b), Heppell et al (2014Heppell et al ( , 2015 and Sylvester-Bradley et al (1997), consisting of values for plant root dynamics and soil characteristics, Table 2.…”
Section: From the Literaturementioning
confidence: 99%
“…Roose and Fowler (2004b) advanced the model by tracking the movement of water and P spatially. In this paper, for the first time, we extend the model of Roose and Fowler (2004b) and Heppell et al (2015) by adding the effect of climate, via surface water flux and xylem pressures as in Heppell et al (2014). This extension allows comparison of the model output, plant P uptake (kg P ha −1 ), against two sets of field trial data for barley, for different environmental conditions.…”
Section: Introductionmentioning
confidence: 98%